2021
DOI: 10.3389/fcvm.2021.738817
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Neutrophil to Lymphocyte Ratio and Myocardial Injury in Population Exposed to High Altitude

Abstract: Objective: Myocardial injury is a severe complication in population exposed to high altitude. As a new biomarker for inflammatory response, neutrophil to lymphocyte ratio (NLR) has been widely used to predict the prognosis of various diseases. In this study, we intend to explore the risk factors for myocardial injury at high altitude and examine the relationship between NLR level and development of myocardial injury.Methods: Consecutive patients admitted to a secondary general hospital at high altitude from Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Also, an AUC of 0.63 appears moderate for the prediction of overall CTR-CVT, but compared to other studies, investigating the association of NLR with cardiotoxicity under anti-cancer treatment similar values for AUC is reported [ 33 ]. The same applies to studies examining the association of NLR with mortality or myocardial injury in other non-cancer collectives [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, an AUC of 0.63 appears moderate for the prediction of overall CTR-CVT, but compared to other studies, investigating the association of NLR with cardiotoxicity under anti-cancer treatment similar values for AUC is reported [ 33 ]. The same applies to studies examining the association of NLR with mortality or myocardial injury in other non-cancer collectives [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified 11.415 10 9 /L as the cut-off value of NEU by ROC curve analysis. Notably, we tried to investigate the role of NLR, a valuable predictor of inflammation [ 20 , 21 ], in the diagnosis of muscle necrosis. NLR was found to be associated with muscle necrosis in univariate analysis, but it was not an independent risk factor based on logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…MI is a severe complication in population exposed to high altitude and may leads to malignant arrhythmias, heart failure, and even sudden death [6] . Our previous study found that the incidence of MI was as high as 33.2% in population transferring from high altitude [7] .…”
Section: Introductionmentioning
confidence: 94%